Expression analysis of CD63 in salivary neutrophils and the increased level of Streptococcus mutans in severe early childhood caries - Muhammad Luthfi (Dental Journal (Majalah Kedokteran Gigi), 2015)
Background: Severe early childhood caries (S-ECC) and decay exfoliation filling teeth (def-t) >6 is a destructive disease that afflicts teeth, including maxillary anterior teeth. In Indonesia, the prevalence of this disease is still high, for instance in Semarang 2007, the rate reached 90.5% in urban areas and 95.9% in rural areas for early childhood caries which is caused by Streptococcus mutans (S. mutans). Neutrophils are effector cells of innate immunity which become the main component of the very first line of defense against microbes. Purpose: This study analyzed the effect caused by the change of CD63 expression on the surface of salivary neutrophils and the increased level of S. mutans in S-ECC. Method: This study employs observational analytic and cross sectional approach by using T test analysis technique for forty cases of early childhood that had been divided into two groups, first group of twenty children positively diagnosed as S-ECC and second group of twenty children negatively diagnosed as the control group. The sample’s result of gargling with 1.5% NaCl was used for neutrophils isolation and analysis function of salivary neutrophils phagocytosis by using flow cytometry test, while the sample of saliva was used to isolate S. mutans and calculate the level of S. mutans. Result: The expression of CD63+ salivary neutrophils in S-ECC was lower (2.32% ± 0.57) than in caries-free (2.67% ± 0.46), while the level of S. mutans showed that the level was not higher than in S-ECC (9.78 ± 2.22)x105 CFU/ml compared to in caries-free (5.13 ± 1.86)x105 CFU/ml. Conclusion: The low expression of CD63 in salivary neutrophils can lead to the increased level of S. mutans in S-ECC.